Alice Campbell Sitting On a Beach - Unknown:::Creator::::::::::::
Alice Campbell, who was married to Ed Ricketts, sits on a beach with a cigarette in hand. Alice was a 22-year old music-philosophy senior at UC, Berkeley when she met Ricketts in 1947. She was originally from San Luis Obispo.